VALIDITAS BUTIR SOAL IPA FISIKA SMP VII Dr WAHIDIN SUDIROHUSODO - Palma Juanta; Apriani Sijabat; Festiyed Festiyed; Yerimadesi Yerimadesi (Jurnal Tunas Pendidikan, 2023)
The aim of the study was to measure and find out the validity of the points in Science Physics questions for class VII SMP Dr. Wahidin Sudirohusodo regarding the subject matter of temperature and heat through a quantitative descriptive approach and data collection techniques which were carried out using a test technique in the form of temperature and heat questions totaling 25 items in the form of multiple choices. The population used was all students of class VII SMP Dr. Wahidin Sudirohusodo as many as 224 students spread over 7 parallel classes, 40 students were taken randomly. The sampling technique used is simple random sampling. Data were analyzed using the Anates program version 4 for windows. The results showed that the level of validity of the questions was moderate, namely 0.42. Keywords: Validity, Problem, Science Physics